Formulation of the Menu of a General Hospital After Its Conversion to a “COVID Hospital”: A Nutrient Analysis of 28-Day Menus - Detopoulou, Paraskevi; Al-Khelefawi, Zena Hardan; Kalonarchi, Garifallia; Papamikos, Vasilios (Frontiers in Nutrition, 2022)
Aim: The aim of the present study was to modify the hospital menu, so as to increase energy and protein provision in COVID-19 patients. Methods: After the conversion of our hospital to a COVID-19 hospital, eggs and comfort foods such as vanilla pudding were added to the menu to boost energy and protein intake of patients. All meals of the general menu of the hospital, i.e. breakfast, lunch, and dinner were recorded for 14 consecutive days during two periods: pre-COVID-19 and after being converted to a ‘COVID hospital’. The menus were analyzed with the use of USDA database. Results: The total content of energy (1873 ± 87 vs 2489± 137 Kcal), protein (97± 11 vs 126.4± 18.7 g), fat (55± 9 vs 74.1± 12.8 g), and carbohydrate (241.0± 16.0 vs 323.0±16.0 g) of the provided menus was increased in the COVID-19 period. Moreover, changes were evident in some micronutrients, such as calcium, iron, magnesium, choline, vitamin C, vitamin A, B-vitamins and vitamin D. Conclusions: Simple menu changes and addition of comfort foods can substantially boost the nutrient content of a hospital diet, which in concert with provision of oral nutritional supplements could have an impact on patients’ nutritional status